Mechanical energy and kinematics of diagonal stride technique in world cup ski mountaineering races - Pozzo, R.; Besseghini, A.; Canclini, A.; Baroni, G.; Lindinger, S.; Karczewska-Lindinger, M.; Canclini, A. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: In the last decade, SKIMO skiers improved their technical and physiological performances in all kinds of races. Due to the complex multiparametric environment conditions and the relatively recent development of the discipline, there is a lack of specific studies, especially under race conditions [4]. On the other hand, technique and physiological analysis comparing normal race and treadmill conditions have been undertaken [1-5]. The purpose of this study is to investigate the kinematics and the energy patterns of elite SKIMO skiers during high-level competitions such as Sprint World Cup races.